2022
DOI: 10.3390/molecules27123761
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine Sulfonamides as Novel Potential Anticancer Agents: Cytotoxic and Genotoxic Activities In Vitro

Abstract: In this paper, we present for the first time the evaluation of cytotoxicity and genotoxicity of de novo synthesized pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine sulfonamides MM129, MM130, and MM131 in human tumor cell lines: HeLa, HCT 116, PC-3, and BxPC-3. Cytotoxic and genotoxic properties of the tested compounds were estimated using the MTT assay, comet assay (alkaline and neutral version), and γ-H2AX immuno-staining. Examined sulfonamides exhibited strong anticancer properties towards tested cells in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Furthermore, incubation of colon cancer cells with MM131 —another pyrazolo[4,3- e ]tetrazolo[1,5- b ][1,2,4]triazine sulfonamide—induced apoptosis of DLD-1 and HT-29 cells with observed down-regulation of mTOR kinase, soluble intercellular adhesion molecule-1 (sICAM-1), and cathepsin, together with up-regulation of beclin-1 B [ 33 ]. We have also shown, with the use of an alkaline/neutral version of the comet assay and γ-H2AX staining, that MM129 , MM130 , and MM131 sulfonamides exhibited genotoxic activity in four investigated cancer cell lines (HeLa, HCT-116, PC-3, and BxPC-3) [ 34 ]. The occurrence of DNA damage following exposure to genotoxic agents would normally trigger the DDR responsible for the activation of DNA repair mechanisms or elimination of the severely damaged cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, incubation of colon cancer cells with MM131 —another pyrazolo[4,3- e ]tetrazolo[1,5- b ][1,2,4]triazine sulfonamide—induced apoptosis of DLD-1 and HT-29 cells with observed down-regulation of mTOR kinase, soluble intercellular adhesion molecule-1 (sICAM-1), and cathepsin, together with up-regulation of beclin-1 B [ 33 ]. We have also shown, with the use of an alkaline/neutral version of the comet assay and γ-H2AX staining, that MM129 , MM130 , and MM131 sulfonamides exhibited genotoxic activity in four investigated cancer cell lines (HeLa, HCT-116, PC-3, and BxPC-3) [ 34 ]. The occurrence of DNA damage following exposure to genotoxic agents would normally trigger the DDR responsible for the activation of DNA repair mechanisms or elimination of the severely damaged cell.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular dynamics simulation suggested that the tested compounds bind strongly and durably with molecular targets and may exert an anti-cancer effect through their inhibition [ 19 ]. Furthermore, structurally similar compounds MM129 , MM130 , and MM131 exhibited cytotoxic activity with IC 50 concentrations of 0.17–1.15 μM in four cancer cell lines (HeLa, HCT 116, PC-3, and BxPC-3) and genotoxic activity, as indicated by alkaline/neutral comet assays and γH2AX staining [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high pro-oxidative activity of tested triazine derivatives is consistent with the data obtained from our previous studies, where examined compounds exhibited high genotoxicity against the same cancer cell lines. Similarly to the genotoxicity studies, MM131 showed the most potent pro-oxidative potential among the tested compounds [63]. Furthermore, research has shown that the accumulation of ROS-related damages in lipids, proteins, and DNA may be responsible for the suppression of tumor cell proliferation and growth via cell cycle arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, the investigated compounds were noticeably less cytotoxic toward normal cells-human foreskin fibroblast (Hs27) and human peripheral blood mononuclear cells (PBMCs). The IC 50 values obtained in the MTT assay were shown in the Supplementary Material (Table S1) [63]. Therefore, we decided to investigate the pro-oxidative and pro-apoptotic properties of three novel derivatives of pyrazolo-triazine sulfonamides MM129, MM130, MM131 against four adherent human cancer cell lines-HeLa, HCT 116, PC-3, and BxPC-3.…”
Section: Introductionmentioning
confidence: 99%